The Scientific Approach to Cultivating Scientific Attitudes in Early Childhood - sum, theresia alviani (THUFULA, 2025)
This study examines how the scientific approach is implemented in early childhood education under resource constraints. Using a qualitative case study design, data were gathered from educators at ten institutions over three months (January–March 2024) through interviews, classroom and outdoor observations, and document analysis, and were analyzed using the Miles and Huberman framework. Findings show that while teachers possess a reasonable conceptual grasp of the scientific approach, enactment is inconsistent. Institutions lack dedicated laboratory spaces and rely largely on simple, introductory activities; however, natural settings such as school gardens and spacious grounds are leveraged to sustain observation- and inquiry-based learning. Teachers commonly use big books as primary materials, with infrequent use of online resources due to limited facilities. Curricular goals referencing critical thinking and problem solving are not consistently realized in practice; teacher-led questioning predominates, interdisciplinary integration is minimal, and assessment relies heavily on products rather than projects or presentations. Time structures (3–4 hour daily schedules) and significant budget limitations further restrict routine experimentation and exploration, as well as opportunities for sustained professional development. Notwithstanding these constraints, educators creatively employ natural and recycled materials and selectively integrate digital media. The study concludes that maximizing the potential of the scientific approach requires coordinated support—adequate funding, flexible scheduling, enriched learning environments, and structured, ongoing teacher professional development through collaboration among government, educational institutions, and external partners.